1994
DOI: 10.1136/hrt.71.2.182
|View full text |Cite
|
Sign up to set email alerts
|

Changes in pulmonary venous flow pattern during early neonatal life.

Abstract: Objective-To investigate serial changes in the pattern of flow in the pulmonary vein during the early neonatal period. Methods-Pulsed Doppler echocardiography was used to measure flow in the right upper pulmonary vein in 26 normal newborn infants. Peak flow velocity during systole (S) and diastole (D) and flow velocity at indents between the systolic and diastolic fraction (0) and between the diastolic and systolic fraction (X) were measured 1, 4-8, 24, and 96 hours after birth. The heart rate and diameter of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…The Doppler study showed an almost continuous flow between the systolic and diastolic deflections of the pulmonary flow in G1 patients, probably due to the presence of anterograde flow during the entire cardiac cycle resulting from the increased pulmonary flow. This was previously reported by Agata et al 8 in a study with pulsed Doppler in newborn infants. Those authors observed in the first hour of life an almost continuous pulmonary venous flow of higher velocity, similar to that obtained in situations of congenital obstruction of the pulmonary veins, and compared it with the flow obtained 24 hours later, which was intermittent and with a lower velocity, similar to the flow in adults.…”
Section: Discussionsupporting
confidence: 80%
“…The Doppler study showed an almost continuous flow between the systolic and diastolic deflections of the pulmonary flow in G1 patients, probably due to the presence of anterograde flow during the entire cardiac cycle resulting from the increased pulmonary flow. This was previously reported by Agata et al 8 in a study with pulsed Doppler in newborn infants. Those authors observed in the first hour of life an almost continuous pulmonary venous flow of higher velocity, similar to that obtained in situations of congenital obstruction of the pulmonary veins, and compared it with the flow obtained 24 hours later, which was intermittent and with a lower velocity, similar to the flow in adults.…”
Section: Discussionsupporting
confidence: 80%
“…The pulmonary venous flow wave pattern of this kind is not established immediately after birth. Agata et al [19] reported on pulmonary venous flow wave patterns in early neonates and showed that the flow was continuous with a very high velocity. The velocity at atrial contraction was also forward toward the left atrium.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in pulmonary venous flow occurs immediately after birth, 29 and reflects a sudden increase in pulmonary circulatory volume with additional left to right shunting through the PDA. Also, E/Vp decreases with closure of the PDA.…”
Section: Discussionmentioning
confidence: 99%